THE CATALYST : How to Change Anyone's Mind - Berger, Jonah (London : Simon & Schuster, 2020)
Everyone has something they want to change. Marketers want to change their customers' minds and leaders want to change organisations. Start-ups want to change industries and nonprofits want to change the world. But change is hard. Often, we persuade and pressure and push, but nothing moves. Could there be a better way? This book takes a different approach. Successful change agents know it's not about pushing harder, or providing more information, it's about being a catalyst. Catalysts remove roadblocks and reduce the barriers to change. Instead of asking, "How could I change someone's mind?" they ask a different question: "Why haven't they changed already? What's stopping them?" The Catalyst identifies the key barriers to change and how to mitigate them. You'll learn how catalysts change minds in the toughest of situations: how hostage negotiators get people to come out with their hands up and how marketers get new products to catch on, how leaders transform organisational culture and how activists ignite social movements, how substance abuse counselors get addicts to realise they have a problem and how political campaigners change deeply rooted political beliefs.
t 2. Endowment -- t 5. Corroborating evidence.
Includes index
Includes bibliographical references and index.
Keywords: Influence (Psychology); Persuasion (Psychology)